Method for manufacturing a resin prebaked anode and resin prebaked anode

By using a flash curing process to form a hard shell structure on the surface of a prebaked phenolic resin anode, the problem of insufficient bonding strength of phenolic resin is solved, improving production efficiency and product quality while reducing environmental pollution and costs.

CN120590165BActive Publication Date: 2026-11-03SHANDONG SHENGQUAN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510823652.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-18
Publication Date
2026-11-03
Estimated Expiration
2045-06-18

AI Technical Summary

Technical Problem

The existing phenolic resin prebaked anode calcination process suffers from problems such as insufficient phenolic resin bonding force, low production efficiency, and serious pollution, resulting in long calcination cycles and poor product quality.

Method used

A hard shell structure is formed on the surface of the resin anode green body by flash curing process. Combined with drying curing and calcination processes, the calcination process is optimized, and the waste heat of the calcination kiln is used for drying, reducing the use of metallurgical coke.

Benefits of technology

It significantly improved product qualification rate and production efficiency, reduced environmental pollution and energy consumption, enhanced product integrity and stability, and reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005458608060000011
    Figure HDA0005458608060000011
  • Figure HDA0005458608060000021
    Figure HDA0005458608060000021
Patent Text Reader

Abstract

The application belongs to the field of preparation of prebaked anodes for aluminum, and discloses a preparation method of resin prebaked anodes and resin prebaked anodes. The resin anode green body is prepared, the surface of the resin anode green body is subjected to flash ignition treatment, then drying and curing are performed, the resin anode preform after drying and curing is preheated, and then is transported to a baking furnace for baking to obtain the resin prebaked anode. The flash ignition treatment process effectively solves the crack and slagging problems caused by insufficient bonding force of phenolic resin in the temperature range of 60-80 DEG C, and improves the integrity and stability of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of prebaked anode preparation for aluminum, specifically relating to the preparation method of resin prebaked anodes and resin prebaked anodes. Background Technology

[0002] In the prebaked anode production industry, coal tar pitch has long held a crucial position as the core binder. However, the traditional prebaked anode roasting process using coal tar pitch as a binder has several significant drawbacks. During roasting, the coal tar pitch undergoes a substantial softening phase, which directly leads to a significantly extended roasting cycle, typically requiring about a month. This lengthy roasting cycle not only occupies production equipment and space resources for an extended period, resulting in low overall production efficiency, but also greatly increases energy consumption and production costs.

[0003] Phenolic resin, with its outstanding advantages such as low pollution emissions, is considered one of the ideal candidate materials to replace coal tar pitch. Theoretically, phenolic resin has great potential for rapid calcination, potentially reducing calcination time to five days, which is significant for improving production efficiency and reducing production costs. However, the unique physicochemical properties of phenolic resin also bring a series of new technical challenges. During the critical stage of green curing, phenolic resin exhibits extremely low viscosity within a temperature range of 60–80℃, resulting in severely insufficient bonding strength to the carbon blocks. In this process, the carbon blocks are prone to cracking, flaking, and other quality problems. These issues not only affect the appearance quality of the prebaked anode but also have a serious negative impact on its internal properties, greatly reducing the product's market competitiveness.

[0004] Therefore, based on the current prebaked anode calcination technology for phenolic resin, developing a new prebaked anode calcination method that can effectively improve the bonding performance of phenolic resin, significantly increase production efficiency, and reduce environmental pollution has become an urgent need for technological innovation in the industry. Summary of the Invention

[0005] Traditional processes for producing prebaked anodes from phenolic resin suffer from problems such as insufficient phenolic resin bonding strength, low production efficiency, and severe pollution. This application provides a method for preparing a prebaked resin anode, and the resulting prebaked resin anode. A flash curing process is used to improve the bonding performance of the phenolic resin.

[0006] In one aspect of this application, a method for preparing a resin prebaked anode is provided, comprising:

[0007] Preparation of resin anode green blanks;

[0008] The surface of the resin anode preform is subjected to flash burning treatment to form a hard shell structure on the surface of the resin anode preform, thereby obtaining a resin anode preform;

[0009] The resin anode preform is dried and cured;

[0010] The dried and cured resin anode preform is then calcined.

[0011] In one embodiment, the raw materials for the resin anode green body include binders and aggregates.

[0012] In one embodiment, the binder accounts for 5-40% of the weight of the raw materials, preferably 5-20%, more preferably 5-18%; and the aggregate accounts for 60-95% of the weight of the raw materials, preferably 82-95%.

[0013] In one embodiment, the aggregate is selected from petroleum coke, or a mixture of petroleum coke with carbon materials such as graphite fragments and carbon nanotubes; the petroleum coke accounts for more than 50 wt% of the mixture, preferably more than 80 wt%.

[0014] In one embodiment, the aggregate may also contain waste prebaked anodes.

[0015] In one embodiment, the binder contains phenolic resin and coal tar pitch.

[0016] In one embodiment, the coal tar pitch accounts for less than 5 wt% of the raw material, preferably less than 2 wt%, and more preferably less than 1 wt%.

[0017] In one embodiment, the adhesive is a phenolic resin.

[0018] In one embodiment, the phenolic resin may be one or more of the phenolic resins commonly used in the art, such as biomass-modified phenolic resin, asphalt-modified phenolic resin, coal tar-modified phenolic resin, alkylphenol-modified phenolic resin, and rubber-modified phenolic resin.

[0019] In one embodiment, the temperature of the flash treatment is 300–500°C.

[0020] In one embodiment, the number of flash treatments is 2 to 3.

[0021] In one embodiment, during multiple flash treatments, the time interval between two adjacent flash treatments is 10 to 30 minutes.

[0022] In one embodiment, the thickness of the hard shell layer on the surface of the resin anode preform is 1 to 3 mm.

[0023] In one embodiment, the hardness of the hard shell layer on the surface of the resin anode preform is 20-37 MPa, more preferably 28-32 MPa.

[0024] In one embodiment, drying and curing the resin anode preform includes:

[0025] The resin anode preform is placed inside the cover;

[0026] A heating operation is performed on the resin anode preform covered by the cover.

[0027] In one embodiment, a contact interface is formed between the cover and the resin anode preform, characterized by a continuous, seamless fit without macroscopic gaps.

[0028] In one embodiment, a contact interface is constructed between the cover and the resin anode preform. This interface is characterized by a discontinuous bonding morphology with macroscopic gaps, and the macroscopic gaps are filled with high-temperature resistant particles at the contact interface to make it exhibit a continuous bonding morphology.

[0029] In one embodiment, the high-temperature resistant particulate matter is, for example, metallurgical coke.

[0030] In one embodiment, the material of the cover is selected from silicon carbide and stainless steel, preferably silicon carbide.

[0031] In one embodiment, the temperature set for the heating operation is 140–220°C.

[0032] In one embodiment, the heating operation lasts for 10 to 24 hours.

[0033] In one embodiment, drying and curing the resin anode preform includes:

[0034] The resin anode preform is covered with a heat-carrying filler, which provides the necessary heat for drying to the resin anode preform through thermal conduction. Furthermore, the filler also has the effect of preventing oxidation of the resin anode preform.

[0035] In one embodiment, the resin anode preform is placed in a sagger for the drying and curing process.

[0036] In one embodiment, the filler is selected from metallurgical coke, river sand, etc.

[0037] In one embodiment, the temperature corresponding to the thermal energy possessed by the filler is 180–220°C.

[0038] In one embodiment, prior to the calcination, the process further includes preheating the dried and cured resin anode preform at a temperature of 300–800°C.

[0039] In one embodiment, calcining the dried and cured resin anode preform includes a calcination stage and a cooling stage.

[0040] In one embodiment, the maximum temperature of the firing stage is at least 1150°C; preferably 1150–1250°C. In this embodiment, to ensure excellent performance of the obtained prebaked anode, the firing stage temperature is not recommended to be lower than 1150°C. However, from an energy-saving perspective, the temperature is not higher than 1250°C; it is understood that temperatures higher than 1250°C are also feasible and can also yield prebaked anodes with excellent performance. In one embodiment, the firing time at the maximum temperature during the firing stage is 10–54 hours.

[0041] In one embodiment, the resin anode preform is placed inside a cover during the calcination of the dried and cured resin anode preform.

[0042] In one embodiment, the firing stage lasts for 30 to 72 hours.

[0043] In one embodiment, the temperature during the cooling phase is 400–1250°C.

[0044] In one implementation, the cooling phase employs natural cooling, air cooling, or forced cooling.

[0045] In one embodiment, the resin anode preform is dried, cured, and calcined using a tunnel kiln.

[0046] In one embodiment, the heating operation is carried out using the low-temperature preheating zone of a tunnel kiln.

[0047] In another aspect of this application, a resin prebaked anode is provided, which is prepared by the above method.

[0048] The beneficial effects of this application are as follows:

[0049] 1. Improve product quality

[0050] By employing a flash curing process, a hard shell structure is formed on the surface of the resin anode preform in advance, effectively overcoming the cracking and slagging problems caused by insufficient bonding strength of phenolic resin in the 60-80℃ temperature range. In some preferred embodiments, the application of the cover body solves the oxidation risk of the resin anode preform during the calcination process, significantly improving the integrity and stability of the product and greatly increasing the yield.

[0051] 2. Improve production efficiency

[0052] By introducing flash curing technology, in some preferred embodiments, the complex and time-consuming step of filling with metallurgical coke in traditional processes can be effectively avoided, significantly saving processing time. Simultaneously, utilizing the waste heat resources of the roasting kiln or furnace for drying operations deeply optimizes the roasting process, drastically reducing the roasting cycle from nearly a month to less than five days. This not only significantly improves the capacity utilization of the roasting kiln or furnace, especially the tunnel kiln, but also helps enterprises double their output within the same production cycle, powerfully enhancing their market responsiveness and overall competitiveness.

[0053] 3. Reduce environmental pollution

[0054] In some preferred embodiments, the use of filler metallurgical coke in traditional processes can be reduced or even eliminated, thereby reducing dust generation and pollutant emissions from metallurgical coke roasting, improving the workshop working environment, and lowering environmental treatment costs. The entire production process is more environmentally friendly, complies with current environmental policy requirements, and is conducive to the sustainable development of enterprises.

[0055] 4. Energy and cost savings

[0056] The process eliminates the need for separate curing and drying of the resin anode green body, and shortens the calcination time, significantly reducing the overall process time, saving production time, and lowering production costs.

[0057] In some implementations, the waste heat from the roasting furnace or kiln is used for drying, achieving energy recycling and reducing energy consumption. Furthermore, protective covers such as silicon carbide covers are reusable, reducing the use of disposable materials and lowering production costs.

[0058] 5. Optimize the performance of electrolytic aluminum

[0059] Resin anodes produced by high-temperature firing result in lower resistivity compared to traditional methods. When applied to aluminum electrolysis, this not only saves electricity but also purifies the molten aluminum, effectively improving the electrolysis process and bringing better economic benefits to aluminum producers. Attached Figure Description

[0060] Figure 1 Photograph of the resin prebaked anode obtained by the method in Example 1;

[0061] Figure 2 Photograph of the resin prebaked anode obtained by the method in Example 6;

[0062] Figure 3 Photograph of the resin prebaked anode obtained by the method in Comparative Example 3;

[0063] Figure 4 Photograph of the resin prebaked anode obtained by the method in Comparative Example 1. Detailed Implementation

[0064] The technical solution of this application will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are only some embodiments of this application, not all embodiments, and are only used to illustrate this application, and should not be regarded as limiting the scope of this application. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturer of the equipment or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0065] To overcome the challenge of poor bonding performance of phenolic resin within a specific temperature range, traditional processes typically involve filling the carbon blocks with metallurgical coke to provide structural support. However, this traditional approach has significant drawbacks: First, the introduction of metallurgical coke filling not only increases the complexity of the production process but also significantly occupies the internal space of the tunnel kiln, resulting in a marked decrease in space utilization and hindering further improvements in kiln production efficiency. Second, the dust pollution generated during the filling process is a prominent issue, and the metallurgical coke may release harmful substances during the high-temperature roasting stage, leading to a deterioration of the overall production environment and a sharp increase in environmental pressure. For example, some prebaked anode manufacturers using this process have long been plagued by dust pollution in their production workshops, resulting in harsh working conditions that pose a potential threat to the health of frontline workers, while also incurring high environmental remediation costs. Furthermore, even with the metallurgical coke filling measure, it is still difficult to effectively prevent the generation of carbon block cracks, leading to a persistently high product defect rate.

[0066] Therefore, this application proposes a method for preparing a resin prebaked anode, which involves curing the surface structure of the resin anode green blank by flash curing and then calcining it.

[0067] In some embodiments, the method for preparing the resin prebaked anode includes:

[0068] Preparation of resin anode green blanks;

[0069] The surface of the resin anode preform is subjected to flash burning treatment to form a hard shell structure on the surface of the resin anode preform, thereby obtaining a resin anode preform;

[0070] The resin anode preform is dried and cured;

[0071] The dried and cured resin anode preform is then calcined.

[0072] In the present application, the applicant unexpectedly discovered that by flash-blanking the surface of the resin anode green blank, the product qualification rate of the resin prebaked anode can be significantly improved, increasing it from about 10% to over 80%, such as 85%, 90%, 95%, or even 98%, 99%, or 100%. Furthermore, flash-blanking also helps improve the performance of the obtained resin prebaked anode, such as its apparent density, compressive strength, resistivity, and ash content.

[0073] In some implementations, after flash curing, drying curing is performed, followed by calcination. The drying curing step can be carried out by steam heating or by making full use of the waste heat of the calcining kiln or furnace, such as using the waste heat of a tunnel kiln for calcination, or a combination of both methods.

[0074] In some implementations, the roasting stage can be carried out using conventional kilns, with tunnel kilns being preferred. The inventors have found that after flash curing, roasting in a tunnel kiln results in shorter roasting time, energy savings, and cost reduction, and the obtained resin prebaked anode has lower resistivity and better performance.

[0075] In some embodiments, the raw materials for the resin anode green body include binders and aggregates.

[0076] In some embodiments, the raw materials for the resin anode preform are dry-mixed and / or wet-mixed using a mixing device; the mixing device is a commonly used or well-known device for those skilled in the art, mainly used for mixing materials with a certain viscosity or high viscosity (such as asphalt), such as a kneader, internal mixer, screw extruder, etc.

[0077] In some embodiments, the adhesive comprises 5-40% by weight of the raw material, for example, any range within the range of 5-30%, 5-20%, 5-18%, or 5-40%; for example, any weight ratio within the range of 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23%, 25%, 27%, 29%, 31%, 33%, 35%, 37%, 39%, 40%, or 5-40%. In some preferred embodiments, the adhesive comprises 5-20% by weight of the raw material; in some more preferred embodiments, the adhesive comprises 5-18% by mass of the raw material. In some embodiments, the aggregate constitutes 60-95% of the raw material by weight, for example, any weight range within the range of 60-95%, 70-95%, 80-95%, 85-95%, or 60-95%; specifically, for example, any weight range within the range of 60%, 63%, 65%, 67%, 69%, 71%, 73%, 75%, 77%, 79%, 81%, 83%, 85%, 87%, 89%, 91%, 93%, 95%, or 60-95%. In some preferred embodiments, the aggregate constitutes 82-95% of the raw material by weight.

[0078] In some embodiments, the adhesive is a phenolic resin.

[0079] In this application, there are no other specific limitations on the selection of the phenolic resin; for example, the phenolic resin can be one or more of the phenolic resins commonly used in the art, such as biomass-modified phenolic resin, pitch-modified phenolic resin, coal tar-modified phenolic resin, alkylphenol-modified phenolic resin, and rubber-modified phenolic resin. In some embodiments, the phenolic resin has a char residue rate of 48%-55%, such as 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, etc.; in some embodiments, the viscosity of the phenolic resin is 16000-19000 cp / 25℃, such as 16000 cp / 25℃, 16500 cp / 25℃, 17000 cp / 25℃, 17500 cp / 25℃, 18000 cp / 25℃, 18500 cp / 25℃, 19000 cp / 25℃, etc. In some embodiments, the phenolic resin has a char residue of 48%-55% and a viscosity of 16,000-19,000 cp / 25°C.

[0080] In some embodiments, the binder is a mixture of phenolic resin and coal tar pitch.

[0081] In some embodiments, the coal tar pitch accounts for less than 5 wt% of the raw materials (e.g., the raw materials include binders and aggregates), preferably less than 2 wt%, and more preferably less than 1 wt%; specifically, it can be 4.8 wt%, 4.5 wt%, 4.2 wt%, 4 wt%, 3.8 wt%, 3.5 wt%, 3.2 wt%, 3.0 wt%, 2.8 wt%, 2.5 wt%, 2 wt%, 1.8 wt%, 1.5 wt%, 1.3 wt%, 1.0 wt%, 0.9 wt%, 0.8 wt%, 0.7 wt%, 0.6 wt%, 0.5 wt%, 0.4 wt%, 0.3 wt%, 0.2 wt%, 0.1 wt%, 0 wt%, etc.

[0082] In some embodiments, the aggregate is selected from petroleum coke, or a mixture of petroleum coke with carbon materials such as graphite fragments and carbon nanotubes. In some embodiments, the petroleum coke accounts for more than 50 wt% of the mixture; in some preferred embodiments, the petroleum coke accounts for more than 80 wt% of the mixture. In some embodiments, the petroleum coke accounts for more than 50 wt%, 52 wt%, 55 wt%, 58 wt%, 60 wt%, 63 wt%, 65 wt%, 67 wt%, 70 wt%, 72 wt%, 75 wt%, 78 wt%, 80 wt%, 83 wt%, 85 wt%, 87 wt%, 90 wt%, 92 wt%, and 94 wt% of the mixture; for example, 51 wt%, 52 wt%, 53 wt%, 54 wt%, and 55 wt%. %, 56wt%, 58wt%, 59wt%, 60wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 69wt%, 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75 wt%, 77wt%, 78wt%, 79wt%, 80wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, etc.

[0083] In some embodiments, the true density of the petroleum coke is 2–2.5 g / cm³. 3 For example, it could be 2g / cm³. 3 2.1g / cm 3 2.2g / cm 3 2.3g / cm 3 2.4g / cm 3 2.5g / cm 3 Or 2-2.5 g / cm 3Any value within the range. In some embodiments, the resistivity of the petroleum coke powder is 300–500 μΩ·m; for example, it can be any value within the range of 300 μΩ·m, 320 μΩ·m, 340 μΩ·m, 360 μΩ·m, 370 μΩ·m, 380 μΩ·m, 390 μΩ·m, 400 μΩ·m, 410 μΩ·m, 420 μΩ·m, 430 μΩ·m, 450 μΩ·m, 470 μΩ·m, 490 μΩ·m, 500 μΩ·m, or 300–500 μΩ·m.

[0084] In one embodiment, the aggregate may also contain waste prebaked anodes, for example, waste prebaked anodes are used as aggregates with a suitable particle size.

[0085] In some embodiments, the temperature of the flash treatment is any temperature range within the range of 300–500°C, 320–480°C, 350–450°C, 370–430°C, 390–410°C, or 300–500°C; for example, the temperature of the calcination treatment is any temperature within the range of 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, or 300–500°C.

[0086] As used in this article, "flash treatment" refers to a non-continuous or short-duration burning process.

[0087] The applicant discovered that at the flash-heating temperature, the yield of the obtained resin prebaked anodes can be significantly improved, increasing the yield from 40-50% to over 80%, such as 85%, 90%, 95%, or even 98%, 99%, or 100%. Furthermore, the flash-heating temperature also helps improve the properties of the obtained resin prebaked anodes, such as their apparent density, pressure resistance, resistivity, and ash content.

[0088] In some implementations, the number of flash treatments is 2 to 3; for example, 2 or 3 times.

[0089] In some embodiments, when the flash treatment is performed multiple times, the time interval between two adjacent flash treatments is any time range within the range of 10-30 min, 12-28 min, 15-25 min, 17-22 min, or 10-30 min; for example, any time interval within the range of 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, or 10-30 min.

[0090] The applicant discovered that, with the number of flash treatments and the time intervals described above, it was possible to significantly improve the product yield of the obtained resin prebaked anodes and ensure that the performance of the obtained resin prebaked anodes (such as their apparent density, pressure resistance, resistivity, and ash content) was excellent.

[0091] In some embodiments, the thickness of the hard shell layer on the surface of the resin anode preform is any thickness within the range of 1–3 mm, 1.2–2.7 mm, 1.5–2.5 mm, 1.8–2.3 mm, or 1–3 mm. For example, it can be any thickness within the range of 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, or 1–3 mm.

[0092] In some embodiments, the hardness of the hard shell layer on the surface of the resin anode preform is any hardness range within the range of 20–37 MPa, 25–35 MPa, 28–32 MPa, or 20–37 MPa; in some preferred embodiments, the hardness of the hard shell layer on the surface of the resin anode preform is 28–32 MPa; in a specific embodiment, the hardness of the hard shell layer on the surface of the resin anode preform is any hardness range within the range of 20 MPa, 21 MPa, 22 MPa, 23 MPa, 24 MPa, 25 MPa, 26 MPa, 27 MPa, 28 MPa, 29 MPa, 30 MPa, 31 MPa, 32 MPa, 33 MPa, 34 MPa, 35 MPa, 36 MPa, 37 MPa, or 20–37 MPa.

[0093] In some embodiments, the resin anode preform can be dried and cured by: covering the resin anode preform with a cover and then performing a heating operation (e.g., steam heating); or by adding a heat-generating (e.g.,) filler into a crucible and performing the heating operation by preheating the filler. The applicant has found that both of the methods listed above can yield high-performance resin prebaked anodes; and the product yield remains at a high level (at least 80%, and even as high as 98%, 99%, or even 100%).

[0094] In some embodiments, the resin anode preform is dried and cured, including:

[0095] The resin anode preform is placed inside the cover;

[0096] A heating operation is performed on the resin anode preform covered by the cover.

[0097] In some embodiments, the drying and curing, as well as the calcination, can all be carried out in a tunnel kiln. For example, the drying and curing takes place in the low-temperature preheating zone of the tunnel kiln; the calcination mainly takes place in the high-temperature zone of the tunnel kiln.

[0098] In some embodiments, a contact interface is formed between the cover and the resin anode preform, characterized by a continuous, seamless fit without macroscopic gaps.

[0099] In some embodiments, a contact interface is formed between the cover and the resin anode preform. This interface is characterized by a discontinuous bonding morphology with macroscopic gaps, and the macroscopic gaps are filled with high-temperature resistant particles at the contact interface to make it exhibit a continuous bonding morphology.

[0100] In some implementations, the high-temperature resistant particulate matter used to fill the macroscopic gaps is, for example, metallurgical coke.

[0101] In some embodiments, the cover is made of silicon carbide. In some embodiments, the cover is made of stainless steel. In some embodiments, the cover is made of a combination of silicon carbide and stainless steel; for example, some areas are made of stainless steel, while other areas are made of silicon carbide. It should be noted that there are no major restrictions on the choice of the cover material; both silicon carbide and / or stainless steel can yield desirable results.

[0102] In some implementations, the temperature set for the heating operation is any temperature range within the range of 140–220°C, 160–220°C, 180–220°C, 200–220°C, or 140–220°C; in a specific embodiment, the temperature set for the heating operation is any temperature range within the range of 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, or 140–220°C.

[0103] In some implementations, the heating operation time is any time range within the range of 10-24h, 10-20h, 10-18h, 10-15h, or 10-24h; for example, it can be any time within the range of 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, or 10-24h.

[0104] In some embodiments, the resin anode preform is dried and cured, including:

[0105] The resin anode preform is covered with a heat-carrying filler, which provides the necessary heat for drying to the resin anode preform through thermal conduction. Furthermore, the filler also has the effect of preventing oxidation of the resin anode preform.

[0106] In some embodiments, the resin anode preform is placed in a sagger for the drying and curing process.

[0107] In some embodiments, the filler is metallurgical coke; in some embodiments, the filler is river sand; in some embodiments, the filler is metallurgical coke and / or river sand.

[0108] In some embodiments, the temperature corresponding to the thermal energy possessed by the filler is any temperature range within the range of 180–220°C, 190–220°C, 200–220°C, 210–220°C, or 180–220°C; in a specific embodiment, the temperature corresponding to the thermal energy possessed by the filler is any temperature range within the range of 180°C, 190°C, 200°C, 210°C, 220°C, or 180–220°C.

[0109] In some embodiments, prior to the calcination, the process further includes preheating the dried and cured resin anode preform at a temperature of 300–800°C, 350–750°C, 400–700°C, 450–650°C, 500–600°C, or any temperature range of 300–800°C; specifically, it can be any temperature within the range of 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 430°C, 460°C, 490°C, 510°C, 530°C, 550°C, 570°C, 590°C, 600°C, 620°C, 640°C, 660°C, 680°C, 710°C, 750°C, 780°C, 800°C, or any temperature range of 300–800°C. It is understandable that in actual operation, the temperature may not be stable at a specific temperature value. For example, it may fluctuate within a small temperature range, such as within a temperature difference of no more than 100℃, no more than 80℃, no more than 60℃, or no more than 50℃. In actual operation, the temperature may also be at a stable temperature point value, as described above.

[0110] In some implementations, the calcination of the preheated, dried, and cured resin anode preform includes a calcination stage and a cooling stage.

[0111] In this application, the firing stage is a gradient heating process. For example, firing at a first temperature for a period of time, continuing to fire at a second temperature for a period of time, and then firing at a third temperature for a period of time, etc.; and the first temperature is lower than the second and third temperatures, and the second temperature is lower than the third temperature, etc. However, in this process, the applicant discovered that the maximum temperature cannot be too low, for example, not lower than 1150°C.

[0112] In some embodiments, the maximum temperature of the firing stage is at least 1150°C; for example, 1150–1200°C, 1150–1250°C, or 1200–1250°C. Further examples include 1150°C, 1170°C, 1190°C, 1210°C, 1230°C, 1250°C, 1270°C, 1300°C, or even higher temperatures. In some embodiments, the firing stage, at the maximum temperature, lasts for 10–54 hours; for example, 10 hours, 13 hours, 16 hours, 19 hours, 22 hours, 25 hours, 28 hours, 30 hours, 33 hours, 36 hours, 39 hours, 42 hours, 45 hours, 48 ​​hours, 51 hours, 54 hours, or any time within the range of 10–54 hours.

[0113] In some embodiments, the resin anode preform is placed inside a housing during the calcination process after drying and curing to further prevent high-temperature oxidation of the resin anode preform.

[0114] In some embodiments, the temperature of the firing stage is 800–1250°C; for example, it can be 800°C, 900°C, 1000°C, 1150°C, 1170°C, 1190°C, 1210°C, 1230°C, 1250°C, etc. In some embodiments, the firing stage time is any time range within the range of 30–72h, 30–66h, 30–60h, 30–54h, 30–48h, 30–42h, 30–36h, or 30–72h; in a specific embodiment, it can be any time range within the range of 30h, 33h, 36h, 39h, 42h, 45h, 48h, 51h, 54h, 57h, 60h, 63h, 66h, 69h, 72h, or 30–72h.

[0115] In some implementations, the temperature during the cooling phase is any time range within the range of 400–1250°C, 400–1150°C, 400–850°C, 400–650°C, 400–550°C, 400–450°C, or 400–1250°C; for example, it can be any temperature within the range of 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1250°C, or 400–1250°C.

[0116] As is known in the art, the cooling stage can be performed using methods familiar to those skilled in the art. In some embodiments, the cooling stage employs natural cooling; in some embodiments, it employs air cooling; and in some embodiments, it employs forced cooling.

[0117] In some implementations, a tunnel kiln is used to dry, cure, and calcine the resin anode preform.

[0118] In some implementations, the heating operation is carried out using the low-temperature preheating zone of a tunnel kiln.

[0119] In another aspect of this application, a resin prebaked anode is provided, which is prepared by the above method.

[0120] Example 1

[0121] A method for preparing a resin prebaked anode includes the following steps:

[0122] Preparation of S1 resin anode green body

[0123] Petroleum coke is added to a kneader and dry-mixed for 15 minutes to obtain a uniformly mixed dry mixture. Phenolic resin is preheated to 30°C and then added to the kneader and wet-mixed with the uniformly mixed dry mixture for 15 minutes to obtain a uniformly mixed paste. Among the raw materials, petroleum coke is 90 wt% and phenolic resin is 10 wt%.

[0124] The uniformly mixed paste is added to a high-pressure vacuum molding machine for molding. The vacuum degree of the high-pressure vacuum molding machine is -0.02MPa and the molding pressure is 1000 tons to obtain the resin anode green body precursor.

[0125] The true density of petroleum coke is 2.08 g / cm³. 3 The powder resistivity is 400 μΩ·m.

[0126] The phenolic resin has a char residue rate of 48% to 55% and a viscosity of 16,000 to 19,000 cp / 25℃.

[0127] S2 flash curing treatment

[0128] The prepared resin anode preform was placed on the worktable, and the anode surface was uniformly flash-treated with a blowtorch. The flame temperature of the blowtorch was controlled at about 400℃, and the distance between the blowtorch and the anode surface was maintained at about 5 cm. Each blow lasted for 3 to 5 seconds, with a 20-minute interval before the next blow. This process was repeated 3 times to form a 2 mm thick hard shell structure on the anode surface. The strength was measured to be about 30 MPa using a concrete rebound hammer, thus obtaining the resin anode preform.

[0129] S3 drying

[0130] After the flash curing process is completed, ensure that the silicon carbide cover is tightly fitted to the anode without leaving large gaps to effectively prevent oxidation.

[0131] The obtained resin anode preform is placed inside a specially designed silicon carbide enclosure. The resin anode preform covered with the silicon carbide enclosure is then fed into the low-temperature preheating zone of a tunnel kiln. This zone is gradually heated from room temperature and eventually maintained between 200±20℃. The resin anode preform remains in this zone for 12 hours, using residual heat for drying, which further cures the phenolic resin and improves the anode strength.

[0132] S4 preheating and high-temperature calcination

[0133] After drying, the resin anode preform enters the preheating zone via the tunnel kiln's conveying system. The preheating zone temperature is 300-800℃, with the temperature gradually increasing from 300℃ to 800℃. Specifically, it is maintained at 300-400℃ for 4 hours, 400-500℃ for 4 hours, 500-600℃ for 5 hours, 600-700℃ for 5 hours, and 700-800℃ for 6 hours to further remove volatile components from the resin and enhance its structural stability.

[0134] When the resin anode preform enters the high-temperature zone, the temperature range of the high-temperature zone is between 800-1250℃. Specifically, it is kept at 800℃-900℃ for 5 hours, at 900-1000℃ for 6 hours, at 1000-1100℃ for 6 hours, at 1100-1150℃ for 6 hours, and at 1150-1250℃ for 13 hours. The total baking time in this high-temperature zone is 36 hours, which completes the baking process of the anode.

[0135] S5 Kiln Exit and Finished Product Processing

[0136] After calcination, the prebaked resin anode is conveyed into the cooling zone, where it is cooled to below 400°C. Once cooled, the silicon carbide cover is removed, yielding the final prebaked resin anode product; see product photos for details. Figure 1 The resulting resin anode has a smooth and even appearance, with no hard shell peeling off or local cracks.

[0137] Example 2

[0138] The preparation process is the same as in Example 1, except that the flame spraying time and number of times are different in the flash curing step. Specifically:

[0139] S2 flash curing treatment

[0140] The prepared resin anode preform was placed on the worktable, and the anode surface was uniformly flash-treated with a blowtorch. The flame temperature of the blowtorch was controlled at about 400℃, and the distance between the blowtorch and the anode surface was maintained at about 5 cm. Each blow lasted for 8 to 10 seconds, with a 20-minute interval before the next blow. This process was repeated twice to form a 1 mm thick hard shell structure on the anode surface. The hardness was measured to be about 30 MPa using a concrete rebound hammer, thus obtaining the resin anode preform.

[0141] The other steps are the same as in Example 1.

[0142] Example 3

[0143] The preparation process is the same as in Example 1, except that the flame spraying time and number of times are different in the flash curing step. Specifically:

[0144] S2 flash curing treatment

[0145] The prepared resin anode preform was placed on the worktable, and the anode surface was uniformly flash-treated with a blowtorch. The flame temperature of the blowtorch was controlled at about 400℃, and the distance between the blowtorch and the anode surface was maintained at about 5 cm. Each blow lasted for 8-10 seconds, with a 20-minute interval before the next blow. This process was repeated 3 times to form a 1 mm thick hard shell structure on the anode surface. The hardness was measured to be about 30 MPa using a concrete rebound hammer, thus obtaining the resin anode preform.

[0146] The other steps are the same as in Example 1.

[0147] Example 4

[0148] The preparation process is the same as in Example 1, except that:

[0149] S3 drying

[0150] After flash curing, the resulting resin anode preform is placed in a specially designed silicon carbide enclosure and heated with steam, with the temperature gradually increasing from room temperature to 150°C for 4 hours for drying and curing.

[0151] Example 5

[0152] The preparation process is the same as in Example 1, except for the drying step, which is as follows:

[0153] S3 drying

[0154] After the flash curing process was completed, the obtained resin anode preform was placed in a silicon carbide crucible without using a silicon carbide cover.

[0155] The hot metallurgical coke from the kiln after the flash treatment is sucked out by a suction crane. The filler temperature is 220±20℃. At the same time, it is loaded into a silicon carbide sagger containing the resin anode preform. The hot filler transfers some of its temperature to the resin anode preform, which plays a role in drying and curing.

[0156] Example 6

[0157] The preparation process is the same as in Example 1, except that the flame temperature in the flash curing step is different, specifically:

[0158] The prepared resin anode preform was placed on the worktable, and the anode surface was uniformly flash-treated using a blowtorch. The flame temperature of the blowtorch was controlled at 300℃, and the distance between the blowtorch and the anode surface was maintained at approximately 5 cm. Each flash lasted 3–5 seconds, with a 20-minute interval before the next flash. This process was repeated three times to form a 2 mm thick hard shell structure on the anode surface. The hardness, measured using a concrete rebound hammer, was approximately 28 MPa, yielding the resin anode preform. See product photos for details. Figure 2 The resulting resin anode has a smooth and even appearance, with no hard shell peeling off or local cracks.

[0159] Example 7

[0160] The preparation process is the same as in Example 1, except that the flame temperature in the flash curing step is different, specifically:

[0161] The prepared resin anode preform was placed on the worktable, and the anode surface was uniformly flash-treated with a blowtorch. The flame temperature of the blowtorch was controlled at around 500℃, and the distance between the blowtorch and the anode surface was maintained at about 5 cm. Each blow lasted for 3 to 5 seconds, with a 20-minute interval before the next blow. This process was repeated 3 times to form a 2 mm thick hard shell structure on the anode surface. The hardness was measured to be approximately 33 MPa using a concrete rebound hammer, thus obtaining the resin anode preform.

[0162] Example 8

[0163] The preparation process is the same as in Example 1, except that the calcination temperature in the high-temperature calcination step is different, specifically:

[0164] When the resin anode preform enters the high-temperature zone, the temperature of the high-temperature zone is 800-1100℃. It is kept at 800℃-900℃ for 8 hours, at 900-1000℃ for 10 hours, and at 1000-1100℃ for 30 hours to complete the anode calcination process.

[0165] Example 9

[0166] The preparation process is the same as in Example 1, except that the calcination temperature in the high-temperature calcination step is different, specifically:

[0167] When the resin anode preform enters the high-temperature zone, it is 800-950℃. It is kept at 800℃-900℃ for 8 hours and then at 900-1000℃ for 52 hours to complete the anode calcination process.

[0168] Comparative Example 1

[0169] The preparation process is the same as in Example 1, except that the resin anode green preform prepared in S1 is directly dried without flash curing. A photograph of the final resin anode product is shown below. Figure 4 The resulting resin anode exhibited obvious localized cracks.

[0170] Comparative Example 2

[0171] The preparation process is the same as in Example 1, except that the flame temperature in the flash curing step is different, specifically:

[0172] The prepared resin anode preform was placed on the worktable, and the anode surface was uniformly flash-treated with a blowtorch. The flame temperature of the blowtorch was controlled at about 270℃, and the distance between the blowtorch and the anode surface was maintained at about 5 cm. Each blow lasted for 3 to 5 seconds, and the next blow was performed after an interval of 20 minutes. This process was repeated 3 times to form a 2 mm thick hard shell structure on the anode surface. The hardness was measured to be about 24 MPa using a concrete rebound hammer, thus obtaining the resin anode preform.

[0173] Comparative Example 3

[0174] The preparation process is the same as in Example 1, except that the flame temperature in the flash curing step is different, specifically:

[0175] The prepared resin anode preform was placed on the worktable, and the anode surface was uniformly flash-treated using a blowtorch. The flame temperature of the blowtorch was controlled at approximately 520℃, and the distance between the blowtorch and the anode surface was maintained at approximately 5 cm. Each flash lasted 3–5 seconds, with a 20-minute interval before the next flash. This process was repeated three times to form a 2 mm thick hard shell structure on the anode surface. The hardness, measured using a concrete rebound hammer, was approximately 38 MPa, thus obtaining the resin anode preform. A photograph of the final resin anode product is shown below. Figure 3 The hard shell of the obtained resin anode is too hard, and there are localized cases of hard shell peeling off.

[0176] Comparative Example 4

[0177] The preparation process is the same as in Example 1, except that the calcination temperature in the high-temperature calcination step is different, specifically:

[0178] When the resin anode preform enters the high-temperature zone, the temperature of the high-temperature zone is maintained at 800℃, and it is baked at this temperature for 72 hours to complete the baking process of the anode.

[0179] Example 10

[0180] The resin prebaked anode is prepared using a ring furnace, specifically as follows:

[0181] S3 drying

[0182] After flash curing, the obtained resin anode preform is placed in a specially made silicon carbide cover and heated with steam, with the temperature gradually increasing from room temperature to 150±10℃ for 4 hours for drying and curing.

[0183] S4 preheating and high-temperature calcination

[0184] After drying, the silicon carbide cover is removed, and the resin anode preform is placed in the ring furnace using a fixture.

[0185] The roasting process for the annular furnace is as follows:

[0186] Temperature range Heating rate (°C / hour) Roasting time (hours) Ambient temperature -300℃ 6 5 300℃-800℃ 8 24 800℃-1200℃ 10 120 Insulate at 1200℃ for 24 hours -- 168

[0187] S5 Kiln Exit and Finished Product Processing

[0188] After calcination, the prebaked resin anode is cooled down to below 400°C in the cooling zone, yielding the final prebaked resin anode product.

[0189] Example 11

[0190] The preparation of resin prebaked anodes using a shuttle kiln is as follows:

[0191] S3 drying

[0192] After flash curing, the obtained resin anode preform is placed in a specially made silicon carbide cover and heated with steam, with the temperature gradually increasing from room temperature to 150±10℃ for 4 hours for drying and curing.

[0193] S4 preheating and high-temperature calcination

[0194] After drying, the silicon carbide cover is removed, and the resin anode preform is placed in a shuttle kiln using a clamp.

[0195] The firing process for the shuttle kiln is as follows:

[0196] Temperature range (°C) Roasting time (hours) Room temperature -200 2 200-300 3 300 constant temperature 4 300-500 3 500 constant temperature 5 500-800 4 800 constant temperature 3 800-950 3 950-1120 3 1120 constant temperature 50

[0197] S5 Kiln Exit and Finished Product Processing

[0198] After calcination, the prebaked resin anode is cooled down to below 400°C in the cooling zone, yielding the final prebaked resin anode product.

[0199] Experimental Example

[0200] 1) Flash curing effect test

[0201] Fifty resin anode preforms from each of the examples and comparative examples were dried. The appearance of the dried resin anode preforms was observed. If cracks or flaking appeared, they were considered unqualified. The pass rate was calculated. The pass rate % = (number of qualified resin anode preforms / total number of resin anode preforms in the experiment) × 100%. The results are shown in Table 1.

[0202] Table 1. Pass rate of dried resin anode preforms

[0203] Example Pass rate, % Example 1 The scrap rate decreased, and the pass rate increased to around 98%. Example 2 The scrap rate decreased, and the pass rate increased to around 80%. Example 3 The scrap rate decreased, and the pass rate increased to around 80%. Example 6 The scrap rate decreased, and the pass rate increased to around 90%. Example 7 The scrap rate decreased, and the pass rate increased to around 88%. Comparative Example 1 The pass rate is around 10%. Comparative Example 2 The pass rate is around 50%. Comparative Example 3 The pass rate is around 40%.

[0204] 2) Test the performance of resin prebaked anodes

[0205] The apparent density, CO2 reactivity, withstand voltage strength, resistivity, and ash content of the resin prebaked anode with a smooth, crack-free, and seamless shape were tested. The results are shown in Table 2.

[0206] The CO2 reactivity, withstand voltage, resistivity, apparent density, and ash content were tested according to the testing methods in YS / T63.12-2024; the resistivity was tested using a resistance tester.

[0207] Table 2 Performance of Resin Prebaked Anodes

[0208]

[0209] Although the embodiments of this application have been described above by way of example, this application is not limited to the specific embodiments and application fields described above. The specific embodiments described above are merely illustrative and instructive, and not restrictive. Those skilled in the art can make many other forms based on the teachings of this specification and without departing from the scope of protection of the claims of this application, and these are all within the scope of protection of this application.

Claims

1. A method for preparing a resin prebaked anode, comprising: Preparation of resin anode green blanks; The surface of the resin anode preform is subjected to flash burning treatment to form a hard shell structure on the surface of the resin anode preform, thereby obtaining a resin anode preform; The resin anode preform is dried and cured; The dried and cured resin anode preform is then calcined. Wherein, the resin is a phenolic resin; The flash burning treatment includes: spraying the surface of the resin anode green body with a flame gun, wherein the flame temperature of the flame gun is 300~500℃, the duration of each flame is 3~10s, the number of flames is 2~3, and the time interval between two adjacent flames is 10~30min.

2. The preparation method according to claim 1, wherein the raw materials for the resin anode green body include binder and aggregate.

3. According to the preparation method of claim 2, the binder accounts for 5-40% of the weight of the raw materials.

4. According to the preparation method of claim 3, the binder accounts for 5-20% of the weight of the raw materials.

5. According to the preparation method of claim 2, the weight ratio of the aggregate in the raw materials is 60-95%.

6. According to the preparation method of claim 5, the weight ratio of the aggregate in the raw materials is 82-95%.

7. The preparation method according to claim 2, wherein the aggregate is selected from petroleum coke, or a mixture of petroleum coke with graphite fragments and carbon nanotubes; and / or, The petroleum coke accounts for more than 50 wt% of the mixture.

8. The preparation method according to claim 7, wherein the petroleum coke accounts for more than 80 wt% of the mixture.

9. The preparation method according to claim 2, wherein the binder contains phenolic resin and coal tar pitch; wherein, The coal tar pitch accounts for less than 5 wt% of the raw materials.

10. The preparation method according to claim 9, wherein the coal tar pitch accounts for less than 2 wt% of the raw materials.

11. The preparation method according to claim 10, wherein the coal tar pitch accounts for less than 1 wt% of the raw materials.

12. The preparation method according to claim 2, wherein the binder is a phenolic resin.

13. The preparation method according to claim 1, wherein the thickness of the hard shell layer on the surface of the resin anode preform is 1~3 mm.

14. According to the preparation method of claim 13, the hardness of the hard shell layer on the surface of the resin anode preform is 20~37 MPa.

15. The preparation method according to claim 14, wherein the hardness of the hard shell layer on the surface of the resin anode preform is 28~32 MPa.

16. The preparation method according to claim 1, wherein the resin anode preform is dried and cured, comprising: The resin anode preform is placed inside the cover; A heating operation is performed on the resin anode preform covered by the cover.

17. The preparation method according to claim 16, wherein the temperature set for the heating operation is 140~220℃; and / or The heating operation lasts for 10 to 24 hours.

18. The preparation method according to claim 16, wherein a contact interface is constructed between the cover and the resin anode preform, the interface being characterized by a continuous, seamless fit without macroscopic gaps; or A contact interface is constructed between the cover and the resin anode preform. This interface is characterized by a discontinuous bonding form with macroscopic gaps. High-temperature resistant particles are used to fill the macroscopic gaps at the contact interface, thereby making it exhibit a continuous bonding form.

19. The preparation method according to claim 18, wherein the high-temperature resistant particulate matter is metallurgical coke; and / or The material of the cover is selected from silicon carbide and stainless steel.

20. The preparation method according to claim 19, wherein the material of the cover is silicon carbide.

21. The preparation method according to claim 1, wherein the resin anode preform is dried and cured, comprising: The resin anode preform is covered with a heat-carrying filler, which provides the heat required for drying to the resin anode preform through thermal conduction.

22. The preparation method according to claim 21, wherein the temperature corresponding to the thermal energy possessed by the filler is 180~220℃.

23. The preparation method according to claim 1, further comprising, before the calcination: The dried and cured resin anode preform is preheated at a temperature of 300~800℃.

24. The preparation method according to claim 1, wherein calcining the dried and cured resin anode preform includes a calcination stage and a cooling stage.

25. The preparation method according to claim 24, wherein the maximum temperature of the firing stage is at least 1150°C; and / or During the firing stage, the firing time at the highest temperature is 10-54 hours.

26. The preparation method according to claim 25, wherein the maximum temperature of the firing stage is 1150~1250℃.

27. The preparation method according to claim 24, wherein the firing stage lasts for 30-72 hours; and / or The temperature during the cooling phase is 400~1250℃.

28. According to the preparation method of claim 1, the resin anode preform is dried, cured and calcined in a tunnel kiln.

29. A resin prebaked anode, wherein the resin prebaked anode is prepared by the preparation method according to any one of claims 1 to 28.

Citation Information

Patent Citations

  • Pre-baked anode taking phenolic resin as adhesive and manufacturing method of pre-baked anode

    CN115521144A

  • Aluminum deposition and anodization on a metal substrate

    US20180245232A1